DandeLiion v1: An Extremely Fast Solver for the Newman Model of Lithium-Ion Battery (Dis)charge. Issue 6 (24th June 2021) - Korotkin, Ivan; Sahu, Smita; O'Kane, Simon E. J.; Richardson, Giles; Foster, Jamie M.
Abstract : DandeLiion (available at dandeliion.com ) is a robust and extremely fast solver for the Doyle Fuller Newman (DFN) model, the standard electrochemical model for (dis)charge of a planar lithium-ion cell. DandeLiion conserves lithium, uses a second order spatial discretisation method (enabling accurate computations using relatively coarse discretisations) and is many times faster than its competitors. The code can be used "in the cloud" and does not require installation before use. The difference in compute time between DandeLiion and its commercial counterparts is roughly a factor of 100 for the moderately-sized test case of the discharge of a single cell. Its linear scaling property means that the disparity in performance is even more pronounced for bigger systems, making it particularly suitable for applications involving multiple coupled cells. The model is characterised by a number of phenomenological parameters and functions, which may either be provided by the user or chosen from DandeLiion's library. This library contains data for the most commonly used electrolyte (LiPF6 ) and a number of common active material chemistries including graphite, lithium iron phosphate (LFP), nickel cobalt aluminum (NCA), and a variant of nickel cobalt manganese (NMC).